Math, asked by pikaminati, 7 months ago


If a, b are the roots of the equation x2 - 2x + 3 = 0. Then the equation whose roots are
P = -3a2 + 5a - 2 and Q = B3-B2 + B + 5 is
(A) x2 + 3x + 2 = 0
(B) x2 – 3x - 2 = 0
(C) x2-3x + 2 = 0
(D) none of these​

Answers

Answered by pranay00000
0

Answer:

Since α,β are the root of equation x

2

−3x+5=0

So, α

2

−3α+5=0

β

2

−3β+5=0

∴α

2

−3α=−5

β

2

−3β=−5

Putting in (α

2

−3α+7) & (β

2

−3β+7) ....... (1)

−5+7,−5+7

∴ 2 and 2 are the roots

∴ The required equation is x

2

−4x+4=0

Similar questions